2015
DOI: 10.1515/msp-2015-0042
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and modification of reduced graphene oxide aerogels for biofuel cell applications

Abstract: We have carried out the preparation of reduced graphene oxide aerogels using eco-friendly method that is based on the Hummers method of graphite oxidation without the use of NaNO 3 that produces toxic gases. To obtain a porous 3D structure of reduced graphene oxide, we performed the hydrothermal reduction at elevated temperature. We also prepared the rGO aerogel/CNT composite using multiwalled carbon nanotubes as linkers. The rGO aerogels are promising materials as they possess good electrical conductivity (up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Graphene-based electrodes modified with bioelectrocatalytic enzymes have been tested for their use in biofuel cells. [6][7][8][9] Following our recent activity in preparing implantable biofuel cells operating in vivo, [10][11] we assembled a biofuel cell using graphene-modified electrodes. The present paper reports on preliminary results demonstrating non-mediated electron transport between immobilized enzymes and graphene-modified electrodes potentially applicable in future implantable bioelectronics devices.…”
mentioning
confidence: 99%
“…Graphene-based electrodes modified with bioelectrocatalytic enzymes have been tested for their use in biofuel cells. [6][7][8][9] Following our recent activity in preparing implantable biofuel cells operating in vivo, [10][11] we assembled a biofuel cell using graphene-modified electrodes. The present paper reports on preliminary results demonstrating non-mediated electron transport between immobilized enzymes and graphene-modified electrodes potentially applicable in future implantable bioelectronics devices.…”
mentioning
confidence: 99%
“…Each of the Raman spectra obtained in this study revealed carbonaceous characteristic peaks, commonly referred to as the G and 2D (G’) bands at ca. 1580 and 2690 cm –1 , respectively. The spectra obtained in this study revealed that the graphene component of the AM-G M s was composed of multilayer graphene sheets, which were evidenced in the highly symmetrical 2D (G’) band peak. Furthermore, there was a distinct lack of the characteristic “shoulder”, which was observed in the case of graphite. , The large D band that was prominent in the Raman spectra indicated a high number of edge plane-like sites .…”
Section: Resultsmentioning
confidence: 63%
“…Each of the Raman spectra obtained in this study revealed carbonaceous characteristic peaks, commonly referred to as the G and 2D (G') bands at ca. 1580 cm -1 and 2690 cm -1 , respectively [30][31][32][33][34] . The spectra obtained in this study revealed that the graphene component of the AM-GMs was comprised of multi-layer graphene sheets, which was evidenced in the highly symmetrical 2D (G') band peak.…”
Section: Resultsmentioning
confidence: 99%
“…The relative intensity ratio between D and G peaks in the rGO sample is smaller than in the GO sample, indicating that rGO and G have less disorder. The C-C stretching vibration region (1300 to 1650 cm -1 ) and the C-H bending in-plane vibration region (1000 to 1500 cm -1 ) for rGO, however, overlap with graphene modes [31]. Apparently, in Fig 9, the Raman spectrum of the pristine graphene shows an intensive G-band at ~1584 cm -1 .…”
mentioning
confidence: 87%